Electronic patient reported outcomes to support care of patients with traumatic brain injury: PRiORiTy study qualitative protocol. Issue 1 (25th January 2019) - Retzer, Ameeta; Turner, Grace M; Slade, Anita; Kyte, Derek; McMullan, Christel; Jones, Laura; Belli, Antonio; Calvert, Melanie
Abstract : Introduction: Traumatic brain injury (TBI) represents a major health and socioeconomic problem internationally. The expansive nature of injuries results in a heterogeneous population. The degree and type of long-term impacts following TBI and improvement following injury are highly variable. The use of electronic Patient Reported Outcomes Measures (ePROMs) could help identify residual impacts of TBI and support patient management and care. The Patient Reported Outcomes Research in Trauma study is a qualitative study exploring the long-term symptoms and impacts that are experienced by those with TBI and the potential utility of an ePROM platform to collect real-time information on patient symptoms and quality of life to inform treatment and identify support needs. Methods and analysis: Semi-structured telephone and face-to-face interviews will be conducted with approximately 30–40 individuals recruited from five groups: (1) people with TBI; (2) carers and relatives of individuals with TBI; (3) TBI healthcare professionals; (4) researchers and (5) third sector staff members and volunteers working with those with TBI. Data will be analysed using directed thematic analysis employing an iterative coding frame that will be modified as analysis progresses. Intercoder triangulation will be employed to enhance credibility. Ethics and dissemination: This study was approved by the West Midlands—Black Country Research Ethics Committee (Ref: 18/WM/0033). Findings will be disseminated via conference presentations, peer-reviewed journals, social media (@CPROR_UoB; http://www.birmingham.ac.uk/cpror ) and the National Institute for Health Research Surgical Reconstruction and Microbiology Research Centre.